2019
DOI: 10.3389/fpsyg.2019.02670
|View full text |Cite
|
Sign up to set email alerts
|

Do Gross and Fine Motor Skills Differentially Contribute to Language Outcomes? A Systematic Review

Abstract: Background: Changes in motor development provide children with new learning opportunities to interact with objects, their environment, and with caregivers. Previous research finds that both gross and fine motor skills are predictive of later language outcomes across early infancy and childhood. However, gross and fine motor skills afford different types of interactions. Thus, gross and fine motor skills may potentially differ in the developmental trajectories through which cascading changes in language may occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 56 publications
2
48
0
1
Order By: Relevance
“…Of the eight types of existing observational designs (Anguera et al, 2018b), we employed a Nomothetic/Punctual/Multidimensional design. It was: "Nomothetic" because various units of observation were studied (43 children); "Punctual" because for each child, an observation session was carried out to study each of the motor skills of interest in the study; and "Multidimensional" because different response levels were observed, that is, distinct aspects were observed regarding the gross and fine motor skills, thereby following the theoretical proposal of distinct authors (Matheis and Estabillo, 2018;Gonzalez et al, 2019;Goodway et al, 2019;Meylia et al, 2020). These response levels are reflected in the observation instrument used (available in the Supplementary Material).…”
Section: Methodology and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eight types of existing observational designs (Anguera et al, 2018b), we employed a Nomothetic/Punctual/Multidimensional design. It was: "Nomothetic" because various units of observation were studied (43 children); "Punctual" because for each child, an observation session was carried out to study each of the motor skills of interest in the study; and "Multidimensional" because different response levels were observed, that is, distinct aspects were observed regarding the gross and fine motor skills, thereby following the theoretical proposal of distinct authors (Matheis and Estabillo, 2018;Gonzalez et al, 2019;Goodway et al, 2019;Meylia et al, 2020). These response levels are reflected in the observation instrument used (available in the Supplementary Material).…”
Section: Methodology and Designmentioning
confidence: 99%
“…Motor skills include the movement and coordination of one's muscles and body (Matheis and Estabillo, 2018). They are classified into two groups: (1) Gross motor skills and (2) Fine motor skills (Gonzalez et al, 2019;Goodway et al, 2019;Meylia et al, 2020). (1) Gross motor skills refer to developmental aspects associated with the child's ability to move using their large muscle groups to perform activities such as walking and jumping.…”
Section: Introductionmentioning
confidence: 99%
“…These larger cortical divisions include specific brain regions traditionally associated with language, such as Broca's area (within the insular and medial/inferior frontal cluster) and the supramarginal gyrus (as part of the occipital and parietal cluster), which has been implicated in studies of toddlers with developmental language disorders using MRI (Morgan et al 2016). Moreover, the contribution of the cortical primary motor areas complements the association between motor skills and language in both ASC and the general population (Bedford et al 2016;Gonzalez et al 2019), whereby better motor development is related to better language development, revealing a close relationship between these seemingly 'independent' domains.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, accumulative evidence highlights the beneficial effects of FMS competence on wider aspects of child development. FMS have been linked to key elements of school readiness [ 15 ], including cognitive [ 16 , 17 ], language [ 18 ], and social [ 19 ] outcomes. Moreover, FMS level has been found to be inversely related with body mass index (BMI) [ 20 , 21 ] and positively associated with physical activity behaviors in preschool children [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%